Some aspects of occupational safety at mining enterprises - Cheltybashev, A. A.; Sudak, S. N.; Karnachev, I. P. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2022)
Introduction. The article discusses the issues of labor protection at mining enterprises. Timely analysis and elaboration of measures to prevent them can reduce the risks of major accidents with a large number of victims. Problem Statement . It is necessary to choose the most effective measures to improve the level of industrial safety at mining enterprises based on a ready-made conceptual model of hazardous phenomena and accidents. Theoretical Part. To solve this problem, the article considers a ready-made conceptual model of hazardous phenomena and accidents that may occur in mines as a result of non-compliance with the requirements of occupational safety and industrial safety of enterprises proposed by A. I. Babenko. The analysis of accidents, risk factors, potential dangerous and harmful production factors at the mining enterprise is carried out. Based on the analysis, the most effective measures to improve the level of industrial safety at mining enterprises are proposed. Conclusions. The article considers the issues regulating labor protection at mining enterprises, as well as it identifies industrial risks and options for their elimination through the organization of measures to ensure industrial safety. Based on the results obtained, the most effective means to reduce the risks of hazardous production situations is the use of multifunctional systems to ensure occupational safety and industrial safety of mining enterprises.